The role of minimally invasive plate osteosynthesis (MIPO) technique for treating 3- and 4-part proximal humerus fractures in the elderly – a case study: MIPO for elderly proximal humerus fractures - Attala, Dario; Primavera, Matteo; Di Marcantonio, Arianna; Broccolo , Loris; Oliverio, Francesco Pio; Zoccali , Carmine; Baldi, Jacopo; Biagini, Roberto (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the workProximal humeral fractures incidence in the elderly population is increasing. Treatment management is complicated by fracture complexity and patients' comorbidities. The aim of our prospective study is the outcome evaluation of the role of minimally invasive plate osteosynthesis (MIPO) for elderly patients with a 3- or 4-parts proximal humeral fractures having an intact medial wall. MethodsWe included n=42 unilateral 3- and 4-parts proximal humeral fractures treated with MIPO: 20 4-part fractures and 22 were 3-parts fractures were included. 17 patients identified as male and 25 as female (mean age 84yo).  A trans-deltoid approach has been used with minimal surgical exposure and tissue damage to preserve the local tissue for early shoulder mobilization. ResultsAt follow-up, the DASH recorded mean value was 72, while the Constant mean score was 68. Complications have been recorded in 23,8% of patients with 4-parts fractures having the highest complication frequency. Mean shoulder joint ROM was recorded: anterior elevation 75°, lateral elevation 80°, abduction 90°, intra-rotation 50°, extra-rotation 25°. The following factors were identified influencing the outcome: >8mm calcar fragment, head valgus impaction and periosteal medial hinge preservation. ConclusionsThe increase in population longevity matches the increase in complex humeral fracture frequency. We strongly for management consensus for proximal humerus fracture, in a similar way as for neck femoral fractures. MIPO is excellent in reducing soft tissue damage and complications for elderly patients with limited functional demand.